FRI0031 ASSESSMENT OF EFFICACY, SAFETY AND IMMUNOGENICITY OF A TRIVALENT SPLIT-VIRUS INFLUENZA VACCINE IN PATIENTS WITH RHEUMATIC DISEASES. (June 2019) - Bukhanova, Daria; Belov, Boris; Tarasova, Galina; Gordeev, Andrey; Demidova, Natalia; Erdes, Shandor; Dubinina, Tatiana; Cherkasova, Maria; Diatroptov, Mikhail
Abstract : Background: In current rheumatology practice concurrent infections produce significant negative impact on patients' morbidity, mortality and quality of life. Based on WHO estimations the annual incidence of influenza in adult population amounts to 5-10% worldwide. Influenza can lead to hospitalization (3 to 5 million cases per year) and even death (250-500 thousand cases per year). Flu and its complications rates are higher in patients with rheumatic diseases (RD) as compared to general population. Therefore, prevention of influenza should be viewed as integral part of RD population management. Objectives: To study the safety, efficacy and immunogenicity of inactivated split-virus influenza vaccine in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Methods: 126 subjects (90 females and 36 males, aged 22 - 82 y) with recent acute respiratory viral infections (ARVI) and flu episodes in medical records were enrolled, including 52 RA patients, 34 AS patients and 40 healthy volunteers as the control group. 39 RA pts received methotrexate (MTX), 12 - TNFα inhibitors +MTX, 8 – Leflunomide, 2 – abatacept, 2 – sulfasalazine, 1 – tofacitinib + MTX. 19 AS patients were treated with nonsteroidal anti-inflammatory drugs (NSAIDs), 15 –with TNFα inhibitors. The RD duration ranged from 2 months to 46 years. All participants were injected subcutaneously with one dose (0.5 ml) of the trivalent inactivated influenza vaccine containing the actual influenza virus strains, with ongoing therapy. The control visits were scheduled at baseline, and in 1, 3 and 6 months after vaccination (Visits 0, 1, 2 and 3, respectively). Standard clinical and laboratory tests were performed during each visit. Immunogeniity of vaccine was measured with ELISA test kits. Results: Vaccine tolerability was good in 103 participants (77, 4%). Post-vaccination pain, swelling and redness of the skin up to 2 cm in diameter were registered in 20 cases (15%), low-grade fever, myalgia and malaise were documented in 10 cases (7, 5%). There was no casual relationship between these reactions and principal therapy, therefore, no modifications of therapeutic regimens were required, and complete resolution occurred within 24 hours without additional interventions. No RD exacerbations or new autoimmune disorders were observed during the FUP. At baseline mean pts' DAS28 and BASDAI scores were 3.56 and 3.85, improving up to 1.99 and 3, 09, respectively, 6mo post-vaccination. For the entire FUP there were no cases of influenza or influenza-like illness registered. The proportion of respondents to the vaccine is 70% in the group of patients with RD and 75% in the main group. The level of humoral immune response was not significantly different in the group of patients with RD and in the control. It is noteworthy that there were no significant differences in the level of post-vaccination response after a month (p = 0.6) or after 3 or 6 months of observation. In patients with AS, there were significantly more responses to vaccines in patients with a long duration of the disease and low activity according to the BASDAI index (p <0.05). There was no significant effect of the treatment of RH on the level of post-vaccination response; there were also no differences in the level of post-vaccination response between patients with different RD. Conclusion: Therefore, our results show good tolerability, efficacy and immunogenicity of inactivated split-virus influenza vaccine in RA and AS patients. Future studies on larger patients' populations are warranted for more complete evaluation of vaccine safety and efficacy. Disclosure of Interests: None declared